Salivary oxytocin concentrations in response to running, sexual self-stimulation, breastfeeding and the TSST: The Regensburg Oxytocin Challenge (ROC) study. (December 2015) - Jong, Trynke R. de; Menon, Rohit; Bludau, Anna; Grund, Thomas; Biermeier, Verena; Klampfl, Stefanie M.; Jurek, Benjamin; Bosch, Oliver J.; Hellhammer, Juliane; Neumann, Inga D.
Highlights: OXT concentrations were measured in saliva of healthy adult male and female volunteers before and after stimuli known to increase plasma OXT (i.e. OXT challenges), using a radioimmunoassay. Salivary OXT concentrations increased significantly in response to 10-min of running or sexual self-stimulation. Salivary OXT and cortisol concentrations both increased significantly in response to the Trier Social Stress Test. The stimulus-induced increases in salivary OXT concentrations were quantifiable, rapid and consistent. These results advance the validation of salivary OXT concentration as a valuable tool to monitor global OXT system activity and reactivity. Abstract: Intranasal oxytocin (OXT) application is emerging as a potential treatment for socio-emotional disorders associated with abnormalities in OXT system (re-) activity. The crucial identification of patients with such abnormalities could be streamlined by the assessment of basal and stimulus-induced OXT concentrations in saliva, using a simple, stress-free sampling procedure (i.e. an OXT challenge test). We therefore established the Regensburg Oxytocin Challenge (ROC) test to further validate salivary OXT concentrations as a practical, reliable and sensitive biomarker. OXT concentrations were quantified by radioimmunoassay in samples collected at home by healthy adult male and female volunteers before and after running ("Run") or sexual self-stimulation ("Sex"). In lactating women, salivary OXT concentrations were quantified before, during and after breastfeeding. Salivary OXT along with salivary cortisol and heart rate were monitored in healthy adult participants undergoing the Trier Social Stress Test (TSST). The home-based "Run" and "Sex" challenges as well as the laboratory-based TSST caused quantifiable, rapid, and consistent increases in salivary OXT (approximately 2.5-fold after 10–15 min), which were similar for men and women. Breastfeeding did not result in measurably increased salivary OXT levels, probably because the short pulses of OXT release characteristic for lactation were missed. Taken together, ROC tests reliably assess the responsiveness of the OXT system (i.e., the increase in salivary OXT concentrations as compared to basal levels) to challenges such as "Run" and "Sex" at home or psychosocial stress (TSST) in the laboratory. Further studies with larger sample numbers are essentially needed in order to reveal individual differences in ROC test outcomes depending on, for example, genetic or environmental factors.